Prediabetes: A pragmatic triage for preventive pharmacotherapy - Sanjay Kalra; Saptarshi Bhattacharya; Rakesh Sahay (Journal of the Pakistan Medical Association, 2022)
Prediabetes is a commonly encountered condition that bears a significant risk of progression to diabetes. While lifestyle modification remains the treatment of choice, drug therapy is emerging as a therapeutic option to prevent its progression to diabetes and associated complications. This paper proposes a comprehensive triage system to identify persons with prediabetes who may benefit from preventive pharmacotherapy. Keywords: Acarbose, Diabetes, GLP1RA, Metformin, Obesity, Pioglitazone, Prevention, SGLT2 inhibitors.